PENGARUH ANTARA KETERATURAN PRENATAL YOGA TERHADAP KESIAPAN FISIK DAN PSIKOLOGIS IBU HAMIL TRIMESTER III MENGHADAPI PERSALINAN DI KLINIK HB TAHUN 2023 - Khoiriah, Restu (Politeknik Tiara Bunda, 2024)
Background: Pregnancy and childbirth is a process that can cause changes in the body physiologically in a woman, so some adjustments to these changes are needed. With the problems that occur, physical activity such as exercise during pregnancy can increase stamina, improve mood and reduce anxiety. Prenatal yoga is a form of exercise specifically designed for pregnant women that is beneficial to physical and mental fitness.The purpose of prenatal yoga is to prepare pregnant women both physically, mentally, and spiritually in the face of childbirth. Research Purpose: To determine the effect between the regularity of prenatal yoga on the physical and psychological readiness of third trimeter pregnant women facing labor at the Halo Bayi Clinic in 2023. Research Methods: This research design in quantitative with Case Control method. The population in this study were third trimester pregnant women who did prenatal yoga. Sample was taken using total sampling technique as many as 30 respondents. This research instrument uses a closed questionnaire. Data analysis using chi square test with meaning (α = <0.05). Research Results: The results showed that there was a significant influence between the regularity of prenatal yoga on the physical and psychological readiness of third trimester pregnant women facing labor, (p = 0.000) <α 0.05. Conclusion: There is a relationship between the regularity of prenatal yoga on the physical and psychological readiness of pregnant women